Abundant Nitrate and Nitric Acid Aerosol in the Upper Troposphere and Lower Stratosphere. Issue 18 (20th September 2022) - Yu, Pengfei; Lian, Siying; Zhu, Yunqian; Toon, Owen B.; Höpfner, Michael; Borrmann, Stephan
Abstract: The tropospheric and stratospheric nitrate aerosol is simulated by a sectional aerosol model coupled to the Community Earth System Model. The simulated nitrate mass fractional contribution to aerosols is significantly higher in the upper troposphere and lower stratosphere (UTLS) than that at the surface. Both in situ measurements and simulations show that nitrate aerosol accounts for about 30%–40% of the aerosol mass at the tropopause of the Asian summer monsoon (ASM) region. Furthermore, simulated condensed nitric acid particles account for ∼20% of the annual mean aerosol mass at the tropical tropopause, and over 95% in the UTLS at the South Pole in June‐July‐August. Our study suggests that the extremely cold ambient conditions in the UTLS of the tropics, ASM and polar regions thermodynamically favor the condensation of ammonia and nitric acid. The widely distributed nitrate aerosol in the global UTLS may be overlooked by climate models. Plain Language Summary: The tropospheric and stratospheric nitrate aerosol is simulated by a sectional aerosol model coupled to the Community Earth System Model. Simulated nitrate aerosol mass concentrations are evaluated with observations at the surface and the upper troposphere and lower stratosphere (UTLS). At the global surface, simulated nitrate aerosols account for 6% of non‐dust and non‐sea salt aerosol mass. Significantly higher mass fractions of nitrate are simulated in the UTLS. Our study shows that nitrate accounts for about 30%–40% of the aerosol mass in the Asian tropopause aerosol layer. Furthermore, the model simulations suggested that condensed HNO3 particles contribute to about 20% of the annual mean aerosol burden in the tropical tropopause layer and over 95% in the UTLS of the South Pole in June‐July‐August. We find that the cold conditions in the global UTLS thermodynamically favors the condensation of ammonia and nitric acid. The widely distributed nitrate aerosol in the global UTLS may be overlooked by climate models. Key Points: Nitrate and nitric acid aerosol contribute significantly to the tropical upper troposphere and lower stratosphere (UTLS), Asian summer monsoon and polar regions The cold ambient conditions in the UTLS thermodynamically favor the condensation of nitric acid The simulated aerosol in the global UTLS is primarily composed of the secondarily formed nitrate, sulfate and organics